2016
DOI: 10.3892/ijmm.2016.2645
|View full text |Cite
|
Sign up to set email alerts
|

Advanced glycation end products inhibit testosterone secretion by rat Leydig cells by inducing oxidative stress and endoplasmic reticulum stress

Abstract: Diabetes severely impairs male reproduction. The present study assessed the effects and mechanisms of action of advanced glycation end products (AGEs), which play an important role in the development of diabetes complications, on testosterone secretion by rat Leydig cells. Primary rat Leydig cells were cultured and treated with AGEs (25, 50, 100 and 200 µg/ml). Testosterone production induced by human chorionic gonadotropin (hCG) was determined by ELISA. The mRNA and protein expression levels of steroidogenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 42 publications
3
30
0
1
Order By: Relevance
“…Chronic high glucose and AGEs in diabetes alter normal homeostasis, resulting in an increase in the generation of ROS3233. Treatment with Myr could effectively promote Nrf2 expression and its translocation to the nucleus, which in turn up-regulated HO-1, NQO-1, and γ-GCS to eliminate ROS both in vitro (Fig.…”
Section: Discussionmentioning
confidence: 94%
“…Chronic high glucose and AGEs in diabetes alter normal homeostasis, resulting in an increase in the generation of ROS3233. Treatment with Myr could effectively promote Nrf2 expression and its translocation to the nucleus, which in turn up-regulated HO-1, NQO-1, and γ-GCS to eliminate ROS both in vitro (Fig.…”
Section: Discussionmentioning
confidence: 94%
“…Another study in streptozotocin-induced diabetic animal model showed activation of testicular oxidative stress; mitochondrial cell death and associated p38 MAPK and p53 signaling; and ER stress and associated cell death [36,52]. Similarly, in vitro study, advanced glycation end products, a heterogeneous compound in the progression of diabetes, inhibit the generation of testosterone by upregulation the ER stress related protein Grp78 and CHOP in Leydig cells [53]. Human chorionic gonadotropin (hCG) secreted by placenta, is heterodimeric protein hormone to luteinizing hormone and exogenous hCG has been used clinically to increase plasma testosterone in disease, such as hypogonadotropic hypogonadism, cryptorchidism.…”
Section: Involvement Of Endoplasmic Reticulum Stress In Testis and Gementioning
confidence: 93%
“…As testicular damage due to ageing is considered as a serious complication for males, its delay and prevention become clinically important. As it is known, oxidative stress, increased glycation products and poor antioxidant system appear to be among the main causes of testicular disruption (Güneş, Hekim, Arslan, & Aşcı, ; Zhao, Qi, Hu, Chen, & Liu, ). Therefore, the first aim of this study was to investigate the effect of GAL treatment on prooxidant–antioxidant balance and glycation products in testis tissue.…”
Section: Discussionmentioning
confidence: 99%
“…This decrease is considered to be related to oxidative stress‐induced damage of Leydig cells (Zirkin & Tenover, ). In addition, AGE were also reported to inhibit testosterone production by Leydig cells through inducing oxidative and endoplasmic reticulum stresses (Zhao et al., ). In the present study, serum testosterone levels were also found to decrease in GAL‐treated rats.…”
Section: Discussionmentioning
confidence: 99%